2023
DOI: 10.1038/s42003-023-05338-4
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL2 promotes immune checkpoint inhibitor-related murine autoimmune myocarditis

Haruki Horiguchi,
Tsuyoshi Kadomatsu,
Tomoya Yamashita
et al.

Abstract: Use of immune checkpoint inhibitors (ICIs) as cancer immunotherapy advances rapidly in the clinic. Despite their therapeutic benefits, ICIs can cause clinically significant immune-related adverse events (irAEs), including myocarditis. However, the cellular and molecular mechanisms regulating irAE remain unclear. Here, we investigate the function of Angiopoietin-like protein 2 (ANGPTL2), a potential inflammatory mediator, in a mouse model of ICI-related autoimmune myocarditis. ANGPTL2 deficiency attenuates auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The abnormal expression of CCL18 [206], EOMES (eomesodermin) [207], GZMA (granzyme A) [ [262], IL24 [263], IL9 [264], CHI3L1 [265], CDH1 [266], OLIG2 [267], NKX6-2 [268]. HK2 [269], PNPLA3 [270], CPB2 [271], SEMA4C [272], LRP2 [273], SLC5A11 [274], F11 [275], ANGPTL2 [276] and CYP2A6 [277] genes might be related to the pathophysiology of autoimmune disease. A recent study revealed that SLAMF7 [278], FCRL3 [279], CCR4 [280], GZMA (granzyme A) [281], CCR2 [282], CD48 [283], CD3E [284], CCL4 [285], FASLG (Fas ligand) [286], SLAMF1 [287], CD28 [288], IL7R [289], UBASH3A [290], CD3D [291], ICOS (inducible T cell costimulator) [292], CCL5 [293], CCL3 [294], LTF (lactotransferrin) [295], CTLA4 [296], TNFRSF9 [253], C6 [297], IL5RA [298], IL2RG [299], NPY2R [300], DRD3 [301], CD52 [302], CD163 [303], IQGAP2 [304], PRPH (peripherin) [305], MSR1 [306], HGF (hepatocyte growth factor) [307] [318], HSD17B3 [319], GREM1 [320], ATF3 [321], HK2 [322], TF (transferrin) [323], GLUL (glutamate-ammonia ligase) [324], DMRT2 [325], FN3K [326], TREH (trehalase) [327], ADAMTS4 [328], BMP2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abnormal expression of CCL18 [206], EOMES (eomesodermin) [207], GZMA (granzyme A) [ [262], IL24 [263], IL9 [264], CHI3L1 [265], CDH1 [266], OLIG2 [267], NKX6-2 [268]. HK2 [269], PNPLA3 [270], CPB2 [271], SEMA4C [272], LRP2 [273], SLC5A11 [274], F11 [275], ANGPTL2 [276] and CYP2A6 [277] genes might be related to the pathophysiology of autoimmune disease. A recent study revealed that SLAMF7 [278], FCRL3 [279], CCR4 [280], GZMA (granzyme A) [281], CCR2 [282], CD48 [283], CD3E [284], CCL4 [285], FASLG (Fas ligand) [286], SLAMF1 [287], CD28 [288], IL7R [289], UBASH3A [290], CD3D [291], ICOS (inducible T cell costimulator) [292], CCL5 [293], CCL3 [294], LTF (lactotransferrin) [295], CTLA4 [296], TNFRSF9 [253], C6 [297], IL5RA [298], IL2RG [299], NPY2R [300], DRD3 [301], CD52 [302], CD163 [303], IQGAP2 [304], PRPH (peripherin) [305], MSR1 [306], HGF (hepatocyte growth factor) [307] [318], HSD17B3 [319], GREM1 [320], ATF3 [321], HK2 [322], TF (transferrin) [323], GLUL (glutamate-ammonia ligase) [324], DMRT2 [325], FN3K [326], TREH (trehalase) [327], ADAMTS4 [328], BMP2…”
Section: Discussionmentioning
confidence: 99%
“…SLAMF7 [226], GPR174 [227], FCRL3 [228], SLAMF6 [229], EOMES (eomesodermin) [230], CCR4 [231], CCR2 [232], CD48 [233], CD3E [234], CCL26 [235], CCL4 [236], SLAMF1 [237], CD24 [238], IKZF3 [239], CD2 [240], CD28 [241], IL7R [242], FCGR2B [243], UBASH3A [244], CD1C [245], ICOS (inducible T cell costimulator) [246], CD3G [247], CCL3 [248], LTF (lactotransferrin) [249], GPNMB (glycoprotein nmb) [250], CTLA4 [251], IRF4 [252], TNFRSF9 [253], FCRL5 [254], LAIR2 [255], TAB2 [256], CD52 [257], CD163 [258], MSR1 [259], HGF (hepatocyte growth factor) [260], SIGLEC1 [261], TTR (transthyretin) [262], IL24 [263], IL9 [264], CHI3L1 [265], CDH1 [266], OLIG2 [267], NKX6-2 [268]. HK2 [269], PNPLA3 [270], CPB2 [271], SEMA4C [272], LRP2 [273], SLC5A11 [274], F11 [275], ANGPTL2 [276] and CYP2A6 [277] genes might be related to the pathophysiology of autoimmune disease. A recent study revealed that SLAMF7 [278], FCRL3 [279], CCR4 [280], GZMA (granzyme A) [281], CCR2 [282], CD48 [283], CD3E [284], CCL4 [285], FASLG (Fas ligand) [286], SLAMF1 [287], CD28 [288], IL7R [289], UBASH3A [290], CD3D [291], ICOS (inducible T cell costimulator) [292], CCL5 [293], CCL3 [294], LTF (lactotransferrin) [295], CTLA4 [296], TNFRSF9 [253], C6 [297], IL5RA [298], IL2RG […”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of T cell functions by ICIs can lead to a series of inflammatory adverse events, the precise pathophysiological mechanisms of which are not fully understood [ 124 ]. Current understanding suggests that immune-related adverse events (irAEs) may arise through various pathways involving autoreactive T cells, autoantibodies, and cytokines [ 125 ].…”
Section: Mechanistic Pathways Of Gc Action In Tumor Cellsmentioning
confidence: 99%
“…In addition, mice overexpressing Angptl2 in cardiomyocytes exhibited cardiac dysfunction with lower contractility and lower myocardial energy metabolism, while loss of cardiomyocyte-derived Angptl2 was protective and restored cardiac function ( Tian et al, 2016 ). In murine models of cardiac injury induced by immunotherapy ( Horiguchi et al, 2023 ), septic shock ( Li et al, 2023 ) or the chemotherapeutic drug doxorubicin ( Liu et al, 2022 ), overexpression of ANGPTL2 aggravated cardiac dysfunction and inflammation. ANGPTL2 derived from epicardial adipose tissue could also be involved in fibrotic remodeling of the heart, a substrate for atrial fibrillation ( Abe et al, 2018 ; Kira et al, 2020 ; Takahashi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%